The immune response to Hepatitis C host genetic factors influencing the out-come of Hepatitis C viral infection, in a cohort infected from a single source - Goulding, Carol (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2008)
The Immune response to Hepatitis C; Host genetic factors influencing the out-come of Hepatitis C viral infection, in a cohort infected from a single source. A coordinated response from both the innate and adaptive arms of the immune system is necessary for successful anti-viral immunity. This thesis looks at polymorphisms in genes influencing the innate and in turn the adaptive immune response and the impact that these polymorphisms may have on hepatitis C viral clearance and disease severity. The study group in this thesis provide a relatively unique opportunity to examine the host response to HCV exposure, including those who have cleared the virus spontaneously and those who remained infected. This group were all infected with HCV genotype IB from a single donor and are all of Irish descent, with no other risk factors for liver disease. The fact that a significant number of the identified group had spontaneously cleared the virus meant that they were able to act as controls against those who remained infected.
Keywords: Clinical Medicine, M.D.; M.D. Trinity College Dublin